Quantitative Conformational Analysis of Dissymmetric Macrolides by Molecular Modelling - Belaidi, S.; Lanez, T.; Omari, M.; Botrel, A. (Asian Journal of Chemistry, 2016)
Conformational analysis of dissymmetric macrolides was carried out using molecular modelling (molecular mechanics and molecular dynamics). Calculations indicate that each macrocycle presents eight families of preferential conformers. An important stereoselectivity of the complexed macrocycles was obtained. The Boltzmann distribution of the starting conformations can be used to predict the stereoselectivity of these reactions.